Measuring sustainable tourism lifestyle entrepreneurship orientation to improve tourist experience - Antunes, M.; Dias, Á.; Gonçalves, F.; Sousa, B.; Pereira, L. (Sustainability, 2023)
This study develops a four-item scale to measure the impact of a tourism lifestyle entrepreneur on the touristic experience, and seeks to understand to what extent a tourist perceives, through what is provided, that a tourism business owner, is not a “common entrepreneur”. After an item generation, data was collected from two different surveys with 200 answers, and exploratory and confirmatory factorial analyses were performed to test discriminant and nomological validity. The correlation between the variables was significant at level 0.01 and the coefficients were positive. Cronbach’s Alpha was acceptable with a value of 0.736. The results complemented existing literature on this topic and allowed further research to measure the perception of tourists in regard to tourism lifestyle entrepreneurship. From an interdisciplinary perspective, this manuscript presents insights for entrepreneurial management, tourism marketing and business sustainability. At the end, the limitations of the study are presented, and lines of investigation outlined for future research.